Digital Marketing Strategy in the Industrial Era 5.0: A Systematic Literature Review - Wahyu Rahmadia R; Veri, Jhon (UPI YPTK Journal of Business and Economics, 2025)
The Industry 5.0 era emphasizes the integration of humans with technology in business activities, including digital marketing. This article was created to present a systematic literature analysis on effective strategies in digital marketing in the Industry 5.0 era. This study uses the Systematic Literature Review (SLR) method with a qualitative approach to evaluate the latest trends, strategies, and impacts in digital marketing. Literature searches were conducted on articles from 2015 to 2024 from various academic databases. The results of this study reveal that content editing, social media utilization, and the use of big data are the main strategies that have an impact. In addition, this study also explains the shortcomings of the research and provides real examples of implementation for companies.